Analysis of four coils by inductive powering links for powering bio-implantable sensor - Alghrairi, Mokhalad; Sulaiman, Nasri; Wan Hasan, Wan Zuha; Jaafar, Haslina; Mutashar, Saad (Association for Information Communication Technology Education and Science (UIKTEN), 2022)
The inductive coupling link technique is popularly used for transmitting power in many biomedical applications, where it helps in transferring power to numerous implanted biomedical devices like a wireless pressure sensor system. It has also been noted that the inductive coupling variables significantly affect the coupling efficiency. In this study, the researchers have investigated the inductive coupling link variables for 3 transmitter coils and one receiver coil. They used a resonant frequency of 27 MHz as the operating frequency, based on the Industrial, Scientific and Medical (ISM) band. The experimental results indicated that the Voltage gain (i.e., Vgain) value of the inductive links was dependent on the Coupling Factor (K) existing between every coil and load resistance (i.e., Rload). It was also noted that the value of the Voltage gain increased with an increase in the implanted resistance, based on a constant coupling factor. Furthermore, the simulation results indicated that if the Rload=1000, the Vgain value would be maximal, whereas if Rload = 200Ω, the Vgain value would be minimal and ≈ 5V.These results indicated that the operating system could satisfy all the requirements for powering the implanted sensor biodevices.